A New Marine Biomaterial: The Shell of Mangrove Horseshoe Crabs, Carcinoscorpius rotundicauda (Latreille, 1802) Emphasizing Its Physico-Chemical Characteristics - Wardiatno, Yusli; Riyanto, Bambang; Iskandar, Nopa Aris; Kleinertz, Sonja; Funch, Peter; Kurniawan, Fery (Frontiers in Marine Science, 2021)
The paper aims to elucidate the physico-chemical characteristics of the shell of mangrove horseshoe crabs (Carcinoscorpius rotundicauda) and determine the compilation matrix for the first time. The shell composition matrix of C. rotundicauda has never been studied in detail before, especially the shape of the foam, the chemical composition, the functional groups and the mechanical-physical and thermal properties of the shell. Based on this study, the shell structure of the mangrove horseshoe crab has the potential to be used as the base structure for developing bio-foam insulator material in the future. Therefore, the shell of mangrove horseshoe crabs has a unique natural structure in the form of foam. Its robust and elastic structure has the potential for further development for new marine biomaterials. The formation and composition of horseshoe crab shells foam are also believed to be multifunctional in mobility, used for defense mechanisms and thermal stability. The horseshoe crab samples were collected from Pacitan coastal waters, East Java, Indonesia. The research was conducted using physico-chemical and mechanical-physical analysis. The scanning electron microscopy was used in order to clarify the physico-chemical characteristics. The measurements of the mechanical-physical characteristics included density, unit cell size, and water absorption. The tensile strength and compressive strength were analyzed based on the American Society for Testing Material. Thermal resistance was measured by thermal gravimetric analysis. The results showed that the horseshoe crab shells have a unique structure, where chitin, protein and some minerals are the main chemical elements. The combination and major constituents of the horseshoe crab shell material provide strong and plastic mechanical properties with a maximum tensile strength of 60.46 kPa and maximum compressive strength of 110.55 kPa, water absorption of 0.01195 ± 0.001% and a density value of 0.1545 ± 0.011 g/cm3 as well as the capability to withstand thermal loads with peak decomposition values of 267.4–823.2°C and thermal stability of 60.59%. Using natural marine biomaterials in the future will be beneficial because it leaves no harmful residues and therefore has environmental advantages and at the same time, it is also more cost-effective.